ANALISIS PENGARUH PERSEPSI KUALITAS, PERSEPSI HARGA, CITRA MEREK, PROMOSI, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PT GRAHA SEJAHTERA BAROKAH - Rizqi Maula Afif (Jurnal Akuntansi dan Pajak, 2023)
The aim on this study is to analyze the factors that influence Purchasing Decision on subsidized house developed by PT.GSB ini Jepara. The data were analyzed by using Multiple linear regression analysis. The result of the study showed that Perceived Quality, Perceived Price, Brand Image, Promotion, and Location has a significant effects on consumer Purchasing Decision (57,2%). An increase in these factors will increased chance on consumer purchasing decision to buy the subsidized house of PT GSB. Keywords: Purchase decision, Perceived Quality, Perceived Price, Brand Image, Promotion, Location.